A wake-up call from Chris Freeman's understanding of innovation and innovation systems: challenges for Latin America. Issue 1 (2nd January 2022) - Corilloclla Terbullino, Pavel G.
ABSTRACT: This essay provides a personal account on how my research endeavour drew upon Freeman's seminal ideas regarding four aspects, namely, the broad sense of the national system of innovation (NSI) concept, the definition of innovation as an interactive learning process, the relevance of the science and education subsystems, and the importance of international flows of people, knowledge and technology. Altogether, these ideas supported my building of a conceptual framework to study barriers to university-industry linkages and international partnerships in the context of centres of excellence in Latin American countries (LAC). Freeman's ideas meant a wake-call for understanding innovation in different contexts and an opportunity to build tailored conceptual frameworks that can be applied to LAC.